Gambaran Tingkat Stres Berdasarkan Karakteristik Mahasiswa Semester Awal Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Anak Agung Ayu Lila Paramasatiari; I Gusti Rai Tirta; Anak Agung Istri Shita Darmajayanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Stress is a psychiatric disorder that most often occurs among the community, including students. Early semester students will experience a period of change from the high school environment which can trigger stress. This study aims to identify stress levels based on characteristics including gender, reasons for choosing medical school, place of residence during lectures, high school origin, and academic achievement. The research method used is descriptive research. The population in this study were students in the first semester of the Faculty of Medicine and Health Sciences, Warmadewa University. The sample was determined using a total sampling technique of 157 people. The research took place in November 2021 - May 2022. The data was collected by distributing questionnaires consisting of the DASS-42 questionnaire and the Respondent Characteristics Questionnaire. The results showed that the first semester students of the Faculty of Medicine and Health Sciences, Warmadewa University experienced mild stress as many as 26 people (16.7%), who experienced moderate stress as many as 39 people (25%), who experienced severe stress as many as 15 people (9.6 people). %), and who experienced very severe stress as many as 7 people (4.5%). The results of the research based on the characteristics showed that most of the female respondents experienced moderate stress (27.9%), most of the respondents who chose the medical faculty with their own interests experienced moderate stress (29%), most of the respondents who lived with their parents experienced moderate stress (23.2%), most respondents from Denpasar school experienced mild stress (27.4%), and most respondents who received a very satisfactory rating experienced moderate stress (28.2%).